Menanamkan Nilai Ekologis Toraja Masero melalui Pembuatan Pot bagi Siswa Sekolah Dasar - Chrismesi Pagiu; Lantana D. Rumpa; Yati Dua Padang (Pusat Riset dan Inovasi Nasional, 2025)
This community service activity is a concrete manifestation of the ecological values of Toraja Masero culture, which are oriented toward the preservation of nature and the environment. The method used is demonstration-based approach, in which students are shown directly the step-by-step process of recyclingused or waste paper into functional and decorative flower pots, so that they can observe, imitate, and actively participate in making the pots themselves. Elementary school students not only gain an understanding of the concept of recycling, but also realize that preserving nature can begin with small steps in everyday life. The ecological values emphasized in Toraja Masero—such as protecting the environment, living in harmony with nature, and utilizing resources wisely— are conveyed to students not only in theory but also through real practice. Thus, ecological values in the form of environmental awareness and the responsibility to maintain ecological balance can be strongly instilled in students from an early age.